2005
DOI: 10.1016/j.heares.2004.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Mutant mice reveal the molecular and cellular basis for specific sensory connections to inner ear epithelia and primary nuclei of the brain

Abstract: We review the in vivo evidence for afferent fiber guidance to the inner ear sensory epithelia and the central nuclei of termination. Specifically, we highlight our current molecular understanding for the role of hair cells and sensory epithelia in guiding afferents, how disruption of certain signals can alter fiber pathways, even in the presence of normal hair cells, and what role neurotrophins play in fiber guidance of sensory neurons to hair cells. The data suggest that the neurotrophin BDNF is the most impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 73 publications
(72 reference statements)
2
40
0
Order By: Relevance
“…BDNF (10 ng/ml) and NT-3 10 ng/ ml), required for inner ear development and SGN survival and neurite growth (Fritzsch et al 2004(Fritzsch et al , 2005, added to the culture, promoted afferent-like innervation of HCs by SGNs in the explant, identified by co-immunostaining of CtBP2-positive ribbons apposed by PSD-95-positive endings. The number of PSD-95 puncta and percentage of innervated IHCs were significantly increased in the explants with addition of NTs ( Fig.…”
Section: Neurotrophins Promote Synaptogenesis In Vitromentioning
confidence: 99%
“…BDNF (10 ng/ml) and NT-3 10 ng/ ml), required for inner ear development and SGN survival and neurite growth (Fritzsch et al 2004(Fritzsch et al , 2005, added to the culture, promoted afferent-like innervation of HCs by SGNs in the explant, identified by co-immunostaining of CtBP2-positive ribbons apposed by PSD-95-positive endings. The number of PSD-95 puncta and percentage of innervated IHCs were significantly increased in the explants with addition of NTs ( Fig.…”
Section: Neurotrophins Promote Synaptogenesis In Vitromentioning
confidence: 99%
“…The signaling mechanism associated with this neurite outgrowth from the osseous spiral lamina is probably a result of neurotrophins, growth factors, morphogens, ephrins and/or semaphorins that are expressed in the developing inner ear and have been implicated in guiding auditory innervation (Rubel and Fritzsch, 2002;Webber and Raz, 2006). Significant evidence exists of roles for BDNF, NT3 (also known as NTF3 -Mouse Genome Informatics), semaphorin 3A and BRN3a (also known as POU4F1) Coppola et al, 2001;Farinas et al, 2001;Gu et al, 2003;Fritzsch et al, 2005). BDNF probably plays the dominant role in this neurite outgrowth and extension stage, as multiple studies have shown BDNF to be the most important for short range guidance of SGN afferent fibers extending to hair cells (Pirvola et al, 1992;Wheeler et al, 1994;Coppola et al, 2001;Fritzsch et al, 2005).…”
Section: Neurite Outgrowth and Extension (E18-p0)mentioning
confidence: 99%
“…Our previous study in cats demonstrated a clear cochleotopic order of SG projections in the CN of kittens examined as young as several days prenatal (Leake et al 2002), well before hearing onset. Moreover, studies in mutant mice have demonstrated that at least a rudimentary cochleotopic order is established in connections from the SG, even in the absence of differentiated hair cells (Xiang et al 2003), and central projections can maintain relatively normal organization despite massive rerouting of fibers in the periphery, as seen in Ntf3 tgBDNF mice in which vestibular fibers project to the cochlea (Fritzsch et al 2005).…”
Section: Molecular Mechanisms Neuronal Activity and Tonotopic Map Fmentioning
confidence: 99%
“…Thus, relatively accurate tonotopic maps likely form initially through processes independent of activity and guided by specific molecular mechanisms (Rubel and Fritzsch 2002;Fritzsch et al 2005Fritzsch et al , 2006. Eph/ephrin signaling is of particular interest because of its well-established role in formation of topographic maps in other sensory systems, including the visual system (Feldheim et al 2000), the somatosensory (Prakash et al 2000), and olfactory systems (Cutforth et al 2003).…”
Section: Molecular Mechanisms Neuronal Activity and Tonotopic Map Fmentioning
confidence: 99%